Internet Users’ Valuation of Enhanced Data Protection on Social Media: Which Aspects of Privacy Are Worth the Most? - Mahmoodi, Jasmin; Čurdová, Jitka; Henking, Christoph; Kunz, Marvin; Matić, Karla; Mohr, Peter; Vovko, Maja (Frontiers in Psychology, 2018)
As the development of the Internet and social media has led to pervasive data collection and usage practices, consumers’ privacy concerns have increasingly grown stronger. While previous research has investigated consumer valuation of personal data and privacy, only few studies have investigated valuation of different privacy aspects (e.g., third party sharing). Addressing this research gap in the literature, the present study explores Internet users’ valuations of three different privacy aspects on a social networking service (i.e., Facebook), which are commonly captured in privacy policies (i.e., data collection, data control, and third party sharing). A total of 350 participants will be recruited for an experimental online study. The experimental design will consecutively contrast a conventional, free-of-charge version of Facebook with four hypothetical, privacy-enhanced premium versions of the same service. The privacy-enhanced premium versions will offer 1) restricted data collection on side of the company; 2) enhanced data control for users; and 3) no third party sharing, respectively. A fourth premium version offers full protection of all three privacy aspects. Participants’ valuation of the privacy aspects captured in the premium versions will be quantified measuring willingness-to-pay. Additionally, a psychological test battery will be employed to examine the psychological mechanisms (e.g., privacy concerns, trust and risk perceptions) underlying the valuation of privacy. Overall, this study will offer insights into valuation of different privacy aspects, thus providing valuable suggestions for economically sustainable privacy enhancements and alternative business models that are beneficial to consumers, businesses, practitioners, and policymakers, alike.